Pembinaan kelompok usaha kerajinan tangan anyaman bambu sebagai sumber pendapatan alternatif di desa bungo tanjung kabupaten kerinci propinsi Jambi - Hardi Syafria Husni; Farizaldi Farizaldi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Bamboo woven handicraft is an activity that has long been carried out by a group of women from Bungo Tanjung village, Kerinci regency, Jambi province. However, this craft is not very developed and the resulting product lacks variety and productivity. This work, as an alternative source of income for the community to help the family economy. During the activity, a business group was formed under the name of the Joint Business Group (KUB) Setia woven bamboo crafts. During the implementation of this service activity, it appears that KUB Setia's woven bamboo handicraft business began to develop. This is due to the guidance and assistance of the service team, especially in producing more varied and quality woven products, coaching and expanding the marketing aspect of the product. Likewise, several partner group problems, including: limited equipment owned by partner groups, coloring, refining, product marketing, the service team has been able to assist. Coaching and mentoring of partner groups through the Jambi University Community Service (PPM) program. This activity is very beneficial for the business groups of craftsmen and people who care about woven bamboo crafts. So that it becomes an alternative source of income for partner groups, as well as to realize the tri dharma of higher education through a network of cooperation between related parties. The output of this activity is in the form of woven bamboo handicraft products with more variety and quality, development in terms of marketing. The method of implementing the activities uses a Participatory Rural Appraisal (PRA) approach with institutional implementation with a collective action approach.